2021
DOI: 10.3390/atmos12010071
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Roadside and Urban Background Measurements of Submicron Aerosol Number Concentration and Size Distribution (in the Range 20–800 nm), along with Chemical Composition in Strasbourg, France

Abstract: The adverse health impact of particles and ultrafine particles (UFP) is proven, highlighting the need of measuring the particle number concentration (PNC) dominated by UFP. So far, PNC had never been measured in the Strasbourg urban area (France). The present study on particle size distribution and PNC measurements by an UFP-3031 analyzer was conducted during winter 2019 on a background and a roadside multi-instrumented sites (Black Carbon, chemical speciation, particulate matter 10 μm or less in diameter—PM10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The higher distribution peak at the ~10 nm urban background site (PK site) also shows the influence of traffic emissions (Figure 2b), like the other two sites. Similar patterns have been observed by [51] at ~20 nm and [38] at ~17 nm for an urban background site located close to busy traffic areas. This type of high distribution indicates the contribution of freshly emitted traffic exhaust and more aged traffic [39] as the PK site is located close to the busy arterial roads of the city.…”
Section: Pnds In Different Microenvironmentssupporting
confidence: 83%
“…The higher distribution peak at the ~10 nm urban background site (PK site) also shows the influence of traffic emissions (Figure 2b), like the other two sites. Similar patterns have been observed by [51] at ~20 nm and [38] at ~17 nm for an urban background site located close to busy traffic areas. This type of high distribution indicates the contribution of freshly emitted traffic exhaust and more aged traffic [39] as the PK site is located close to the busy arterial roads of the city.…”
Section: Pnds In Different Microenvironmentssupporting
confidence: 83%
“…It is reminded here that gaseous tailpipe emissions contribute also substantially to ammonium nitrate (Section 10) and SOA (Section 12) formation in urban environments. Furthermore, road transport is a significant source of ultrafine particles (UFP) whose monitoring in French urban environment will be developed at the operational level in coming years [87]. Overall, primary particles related to road transport emissions are assessed to represent about 15% of annual mean PM10 concentrations recorded in French cities [42].…”
Section: Road Transport (Primary Emissions)mentioning
confidence: 99%
“…Controlling the PM mass does not necessarily address the problem of ultrafine particles concentration in the air. A study confirmed that the sources dominating the particle number emissions are different to those dominating the mass emissions [19,20]. The particle number concentration is highly affected by road transport and the mass by aged and transported aerosol [19].…”
Section: Introductionmentioning
confidence: 77%